2018
DOI: 10.1002/jbm.a.36445
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular scaffolds loaded with adipose tissue‐derived stromal cells attenuate development and progression of abdominal aortic aneurysm in rats

Abstract: Abdominal aortic aneurysm (AAA) is the pathological dilation and weakening of the abdominal aorta wall. Inflammation, degradation of the extracellular matrix (ECM) and loss of smooth muscle cells and skewing of their function are pivotal in AAA pathology. We developed a recombinant collagen-based patch (RCP) to provide structural integrity and deliver Adipose tissue-Derived Stromal Cells (ASC) for repair. Patches supported adhesion and function as well as proliferation of ASC. ASC-loaded RCPs or bare patches, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 55 publications
0
18
0
1
Order By: Relevance
“…In this study, a single dose of 1 × 10 6 UC-MSCs were injected intravenously on the 1st postoperative day, which gave rise to considerations about optimal injecting cell amount, along with the frequency and timing of injection. Compared to studies with local implantation of MSCs [ 15 , 20 ], intravenous injection of MSCs represents the minimum invasive systematic route for cellular therapy, and has been previously shown to be effective in different AAA models [ 16 , 18 , 34 ]. In addition, a randomized controlled trail investigating MSCs in small human AAA also applied intravenous administration [ 58 ], which further arise the clinical convenience and feasibility of intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a single dose of 1 × 10 6 UC-MSCs were injected intravenously on the 1st postoperative day, which gave rise to considerations about optimal injecting cell amount, along with the frequency and timing of injection. Compared to studies with local implantation of MSCs [ 15 , 20 ], intravenous injection of MSCs represents the minimum invasive systematic route for cellular therapy, and has been previously shown to be effective in different AAA models [ 16 , 18 , 34 ]. In addition, a randomized controlled trail investigating MSCs in small human AAA also applied intravenous administration [ 58 ], which further arise the clinical convenience and feasibility of intravenous administration.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, preclinical studies have found mesenchymal stem cell (MSC)-based cellular therapy is beneficial to AAA initiation and progression [14][15][16][17][18][19][20][21]. Parvizi et al [20,21] demonstrated that perivascular scaffolds loaded with adipose-derived MSCs could attenuate AAA development, prevent loss of VSMCs, and decrease macrophage infiltration in rats. Sharma et al [19] found that intravenous injection of umbilical cord mesenchymal stem cells (UC-MSCs) attenuates proinflammatory cytokine IL-17 production and protects against AAA formation.…”
Section: Introductionmentioning
confidence: 99%
“…Although the injection of MSCs into the aneurysmal wall holds promise for improving aneurysmal tissue, such direct injection methods come with an increased risk of damaging an already weakened vascular wall. As an alternative method, developing cells loaded onto perivascular scaffolds and applied periadventitialy suppressed development and progression of AAA in rats without the need for direct injection (Parvizi et al, 2018). Although regenerative medicine‐based approaches can potentially treat aneurysms, further studies are required to better understand how MSCs influence aneurysm pathology.…”
Section: Applying Knowledge Of Disturbed Flow Toward Clinical Outcomesmentioning
confidence: 99%
“…Также в патогенезе аневризматической дегенерации аорты лежат инфильтрация воспалительными клетками, разрушение эластина и коллагена матриксными металлопротеиназами, вырабатываемыми макрофагами, некроз гладкомышечных клеток и патологический ангиогенез, что в совокупности приводит к истончению стенки сосуда. Таким образом, развитие аневризмы аорты рассматривается как совокупность дегенеративных процессов вкупе с неблагоприятным ремоделированием в сосудистой стенке [30]. Закономерно, что дисфункциональная жировая ткань путем усиления оксидативного стресса, выработки провоспалительных цитокинов и усиления гипоперфузии вносит значительную долю в патологический процесс.…”
Section: пвжт и аневризмы аортыunclassified